2014
DOI: 10.1016/j.jtcvs.2014.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic effects of fibrinogen concentrate compared with cryoprecipitate in children after cardiac surgery: A randomized pilot trial

Abstract: A large trial comparing fibrinogen concentrate and cryoprecipitate in the management of children with acute acquired hypofibrinogenemia during heart surgery is feasible. The preliminary results of our study showed that the use of fibrinogen concentrate was as efficient and safe as cryoprecipitate in the management of bleeding children undergoing cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 28 publications
1
57
0
6
Order By: Relevance
“…Up to now, the only published randomised controlled trial comparing head-to-head FC and cryoprecipitate included 66 paediatric patients undergoing cardiac surgery developing critical low fibrinogen levels (<1 g/L), showing equal effect on bleeding and RBC transfusion (Galas, de Almeida et al, 2014). Furthermore, and equal increase fibrinogen concentration was observed, but cryoprecipitate also positively affected other coagulation factor levels and measurements of haemostatic capability.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, the only published randomised controlled trial comparing head-to-head FC and cryoprecipitate included 66 paediatric patients undergoing cardiac surgery developing critical low fibrinogen levels (<1 g/L), showing equal effect on bleeding and RBC transfusion (Galas, de Almeida et al, 2014). Furthermore, and equal increase fibrinogen concentration was observed, but cryoprecipitate also positively affected other coagulation factor levels and measurements of haemostatic capability.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a recent systematic review did not find evidence that either cryoprecipitate or FC was superior in terms of efficacy and safety . Both FC and cryoprecipitate have been successfully used to treat acquired hypofibrinogenemia in various settings …”
Section: Discussionmentioning
confidence: 99%
“…49 In this study of 63 patients, 30 were randomized to receive fibrinogen concentrate and 33 to cryoprecipitate if there was diffuse bleeding present requiring hemostatic therapy and the fibrinogen level was <1 g/L. The outcomes of interest were bleeding and transfusion requirements.…”
Section: Cardiac Surgery and Perioperative Usementioning
confidence: 99%
“…The results showed that there was no difference in transfusion requirements at 48 hours or in the frequency of adverse effects between the two groups and the authors recommended a larger trial. 49 In the adult setting, a randomized trial is ongoing, comparing fibrinogen concentrate with cryoprecipitate in patients undergoing cardiopulmonary bypass (TOP-CLOT NCT02540434). Participants will be given cryoprecipitate or fibrinogen concentrate if the ROTEM FIBTEM A10 value is ≤10 mm and microvascular bleeding is present.…”
Section: Cardiac Surgery and Perioperative Usementioning
confidence: 99%